Vitamin D Level, Hormonal and Metabolic Disorders in Polycystic Ovary Syndrome Patients in Thi-Qar Governorate, South of Iraq - Afrah N. Faris, Khalid G. Al-Fartosi, Wassan R. Al-Khafaji (Drugs and Cell Therapies in Hematology, 2021)
The current study aims to estimate vitamin D level and its relationship to hormonal and metabolic abnormalities in women with polycystic ovary syndrome (PCOS). A case-control study was conducted in private health institutions in Thi-Qar Governorate, iraq from March 1, 2021 to September 30, 2021, and included 100 married women with PCOS and infertility and 80 healthy married couples, who diagnosed by gynecologists. Venous blood was sampled from fasting participants for the determination of hormonal and metabolic parameters of this study. The results recorded a significant decline in the levels of vitamin D, estrogen, progesterone and HDL while there was a significant elevation in the levels of AMH, LH, FSH, LH/FSH, total testosterone, free testosteron, BMI, fasting blood sugar, insulin, HOMA-IR, Cholesterol, Triglycerides, LDL and VLDL in the patients with PCOS group compared to the control group (p<0.05). According to the study's findings, anti-Müllerian hormone, level might be considered useful indicator in the early diagnosis of PCOS, as well as treatment targets.The impact of vitamin D deficiency on metabolic and hormonal problems promotes its use in the management of PCOS, as a combination therapies